Fluorescence quenching of benzaldehyde in water by hydrogen atom abstraction - Fletcher, Katharyn M.; Bunz, Uwe H. F.; Dreuw, Andreas (ChemPhysChem, 2016)
We computed the mechanism of fluorescence quenching of benzaldehyde in water through relaxed potential energy surface scans. Time-dependent density functional theory calculations along the protonation coordinate from water to benzaldehyde reveal that photoexcitation to the bright ππ* (S3) state is immediately followed by ultrafast decay to the nπ* (S1) state. Evolving along this state, benzaldehyde (BA) abstracts a hydrogen atom, resulting in a BAH. and OH. radical pair. Benzaldehyde does not act as photobase in water, but abstracts a hydrogen atom from a nearby solvent molecule. The system finally decays back to the ground state by non-radiative decay and an electron transfers back to the OH. radical. Proton transfer from BAH+ to OH− restores the initial situation, BA in water.
Gesehen am 07.12.2017